Review of low emission zones in Europe: Case of London and German cities - Matevž Obrecht; Tajda Potrč; Bojan Rosi (Tehnički Glasnik, 2017)
Over 72% of population in Europe lives in cities nowadays, using a variety of different transportation vehicles for their intercity mobility. A high density of transportation vehicles in cities is a substantial problem in urban areas, since these vehicles are almost exclusively powered by fossil fuels. Fossil fuels have an impact on human health and emit harmful emissions to the environment when burned. Nevertheless, modern lifestyle is highly dependent on fossil fuels and therefore also highly vulnerable in the case of supply shortfalls. Nowadays, environmental problems and the impact of concentrated transport on human health, especially in cities, gained importance and lead to the detection and greater implementation of alternative technologies and advanced sustainable solutions in the field of environmental protection in cities. Since the EU is heavily dependent on imported fossil fuels and has very small oil reserves and a high share of urban population affected by transport pollutants, it is particularly important for the EU to reduce their impact as efficiently as possible and to implement new solutions for a more sustainable future. One such solution is represented with Green zones - areas where we try to minimize harmful transport related environmental and social impacts such as emissions, noise, smog, particle matter, etc. Therefore, this paper consists of an identification and examination of green zones in the selected EU member states (including UK) with special emphasis on German cities and London and analysis of their pros and cons.